UPAYA STRATEGIS MENGGAIRAHKAN PASAR TRADISIONAL SEBAGAI PUSAT PEREKONOMIAN DI KOTA MAGELANG - Haryanti, Ratna (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2025)
Traditional markets in Magelang City face significant challenges from competition with modern markets and the emergence of online shopping, which affect the local economy and community welfare. These markets serve as important centers for economic activity, job creation, price stabilization of essential goods, and support for small and medium enterprises (SMEs). The decline in market activity due to modernization threatens SMEs and access to goods at affordable prices. Government efforts to promote traditional markets remain suboptimal, mainly due to limited involvement and support. This study uses a policy evaluation approach with Grid Analysis and the preparation of policy recommendations with Interpretative Structural Modeling. The main findings of this research reveal that collaboration between the trade and tourism sectors, as well as the use of digital technology to promote traditional markets, are crucial steps to strengthen the existence of traditional markets in Magelang City. This study recommends increasing government efforts to promote traditional markets through collaboration with the tourism sector. These efforts are carried out by integrating sectoral programs between regional government institutions, in order to position traditional markets as the main tourist destination, thereby revealing the number of visitors and various other positive impacts.